Histopathological evaluation of kidney disease in patients with diabetes mellitus (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Non diabetic kidney disease (NDKD), a treatable condition, is common in diabetic patients with atypical clinical presentations. Present study aimed to find out histopathological diagnosis of kidney disease in type 2 Diabetes mellitus with such presentations.Method: This was a hospital based cross sectional study conducted in Nephrology department, Bir hospital, Nepal from Aug 2019 to January 2021. Total 29 diabetic patients with atypical presentations, rapid rise of proteinuria alone (n=5), with microscopic hematuria (n=6), with impaired renal function (n=8) and rapid rise of creatinine with (n=8) or without (n=2) microscopic hematuria were included. The baseline information was recorded and kidney biopsy was performed.Result: The mean age of patients was 52.6±10.4 y and 22(75.9%) were male. Diabetic retinopathy (DR) was absent in 24(82.8%) patients. Presence of NDKD alone was in 6(20.7%) and superimposed on diabetic kidney disease (DKD) in 10(34.5%) with total NDKD in 16(55.2%) and isolated DKD in 13(44.8%) patients. Non diabetic kidney disease were glomerulonephritis 12(75%) with membranous nephropathy 4(25%) and IgA nephropathy 4(25%) patients. The significant difference between NDKD and isolated DKD was only the duration of diabetes < 5 y in 8(61.5%) of isolated DKD and ≥5 y in 13(81.2%) patients with NDKD (p=0.018). Diabetic retinopathy was absent in 6(100%) patients with isolated NDKD, 8(80%) of class III and 5(62.5%) of class IV DKD.Conclusion: Glomerulonephritis is the commonest NDKD in type 2 DM with atypical presentation and advance DKD (Class III & IV) is present even in absence of diabetic retinopathy and short duration of diabetes.